1994
DOI: 10.1089/jop.1994.10.623
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Adhesion to Lens Capsule by LCM 1910, an RGD-Derived Peptide

Abstract: Opacification of the posterior lens capsule, (secondary cataract) , is one of the major complications of extracapsular cataract extraction. The lens epithelial cells remaining after surgery migrate and proliferate along posterior capsule, and give rise to structures such as pearls and cells with contractile properties, which considerably hamper vision. One pharmacological approach aimed at limiting this phenomenon would be to stop this cell migration, thus inhibiting their proliferation. It has been shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Integrin antagonists show clinical promise for the treatment of TGF‐β‐induced EMT‐associated disorders such as inflammation, fibrosis and cancer [106]. Most of the therapeutic approaches currently under investigation target integrin function using anti‐integrin agents including both naturally occurring and engineered peptides that can mimic their RGD ligand, or antibodies that can act as integrin antagonists [107–109]. For example, clinical administration of a peptide antagonist of the αVβ3 receptor successfully inhibits pathological angiogenesis seen in cancer, proliferative retinopathy, rheumatoid arthritis and psoriasis [110, 111].…”
Section: Disease Perspectivesmentioning
confidence: 99%
“…Integrin antagonists show clinical promise for the treatment of TGF‐β‐induced EMT‐associated disorders such as inflammation, fibrosis and cancer [106]. Most of the therapeutic approaches currently under investigation target integrin function using anti‐integrin agents including both naturally occurring and engineered peptides that can mimic their RGD ligand, or antibodies that can act as integrin antagonists [107–109]. For example, clinical administration of a peptide antagonist of the αVβ3 receptor successfully inhibits pathological angiogenesis seen in cancer, proliferative retinopathy, rheumatoid arthritis and psoriasis [110, 111].…”
Section: Disease Perspectivesmentioning
confidence: 99%
“…The expression of β1-integrin is upregulated during epithelial-mesenchymal transitions occurring as a consequence of lens epithelial cell suspension in collagen I gels (Zuk and Hay, 1994) and in response to TGFβ treatment. In fact, it has been proposed that interference with β1-integrin function may be clinically useful to block epithelial-mesenchymal transition of lens cells leading to posterior capsular opacification, a common side effect of modern cataract surgery (Kim et al, 2002;Mathew et al, 2003;Palmade et al, 1994). However, the function of β1-integrin in the lens in vivo is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Palmade et al [24] reported that Ac-Arg-Gly-Asp-NH-CH2-Bzl (LCM 1910) which is an RGD-derived peptide signifi cantly decreased cell attachment on the lens capsule at a concentrationdependent effect, and cell proliferation was decreased on a plastic dish in the presence of LCM 1910 in bovine LEC culture. Sasabe et al [25] reported that 0.5 mg/ml of RGDS and GRGDS RGD peptide showed inhibitory effects on cell attachment in rabbit LEC culture, but 0.5, 1.0 and 2.0 mg/ml of the RGD sequence alone had no effect.…”
Section: Discussionmentioning
confidence: 99%